MANAJEMEN STRATEGI SEBAGAI PILAR UTAMA DALAM TRANSFORMASI SISTEM PENDIDIKAN - Rismiya, Luthfia Amni; Reannisa, Farraz; Lorenta, Hasianna; Aghnia, Syifa Nur; Suriansyah, Ahmad; Purwanti, Ratna (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the role of strategic management as a key pillar in the transformation process of the education system. Educational transformation requires an approach that is not only structural but also strategic, in order to address contemporary challenges systematically and sustainably. This research employs a descriptive qualitative method using a literature review approach, examining various theories and strategic practices in educational management. Data were obtained from various written sources such as academic books, national journals, policy documents, and relevant previous research. The findings indicate that strategic management plays a vital role in defining the direction and goals of education, enhancing the effectiveness of program implementation, promoting transformational leadership, building a culture of quality, and strengthening the synchronization between policies and their implementation in the field. Well-formulated strategies serve as a bridge between national educational visions and operational practices at the institutional level. Leaders with strategic management capabilities are more adaptive to change and capable of creating collaborative and results-oriented work systems. These findings affirm that strategic management is not merely an administrative planning tool, but also the main framework in shaping the future of education. With the implementation of contextual, data-based, and quality-oriented strategies, educational institutions will be better prepared to face policy changes, student needs, and global demands. Therefore, strengthening strategic capacity at both institutional and individual levels is a crucial step in achieving sustainable education reform.